Intrinsic fluorescence studies on saccharide binding to Artocarpus integrifolia lectin. Issue 10 (October 1986) - Sastry, M. V. Krishna; Surolia, A.
Abstract : The combining region of Artocarpus integrifolia lectin has been studied by using the ligand-induced changes in the fluorescence of the lectin. The saccharide binding properties of the lectin show that C-l, C-2, C-4, and C-6 hydroxyl groups of D-galactose are important loci for sugar binding. The α-anorner of galactose binds more strongly than its β-counterpart. Inversion in the configuration at C-4 as in glucose results in a loss of binding to the lectin. The C-6 hydroxyl group is also presumably involved in binding as D-fucose does not bind to the lectin. The lectin binds to the Thomsen-Friedenreich antigen (Galβ(1→3)GalNAc) more strongly than the other disaccharides studied, viz. Gal/β (1→4) Gal and Galβ (1→3) GlcNAc, which are topographically similar to T-antigen. This observation suggests that the combining region of Artocarpus lectin is complementary to that of T-antigen. Solvent accessibility of the protein fluorophores have been probed by the quenching of protein fluorescence by Iodide ion in the absence and presence of sugar. In the presence of sugar a slight inaccessibility of the fluorophores to the solvent has been observed.